2023
DOI: 10.1002/aenm.202301046
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Stability and Efficiency of Perovskite Solar Cells with a Bilayer Hole Transporting Layer of Nickel Phthalocyanine and Poly(3‐Hexylthiophene)

Abstract: To expedite the commercialization of perovskite solar cells (PSCs), researchers are exploring the feasibility of employing nickel phthalocyanine (NiPc) as a hole transport material (HTM) due to its cost‐effectiveness, excellent thermal stability, and suitability for solution coating. However, the low LUMO energy level of the NiPc may limit its ability to block photoelectrons generated in the perovskite layer from recombining with holes, which can reduce the overall efficiency of the solar cell. One solution is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…[98] Kim et al introduced a bilayer HTL consisting of NiPc and P3HT, where a vertical phase separation occurred after optimization leading to a binary formation and achieving a high efficiency of 23.11% PCE. [33] The vertical separation promoted the charge extraction and electron blocking properties of the device and improved the stability response when encapsulated in polyisobutylene, retaining 90% of its initial efficiency after exposure to 85 °C and 85% relative humidity for 1000 h. [33] In a remarkable study, Jeong et al reported the incorporation of gallium (III) acetylacetonate Ga(acac) 3 into P3HT HTL (Figure 3). [32] Ga(acac) 3 interacts with the perovskite surface, passivating the defects on the perovskite surface and reducing the interfacial trap-assisted recombination loss.…”
Section: Inorganic Additivesmentioning
confidence: 99%
See 3 more Smart Citations
“…[98] Kim et al introduced a bilayer HTL consisting of NiPc and P3HT, where a vertical phase separation occurred after optimization leading to a binary formation and achieving a high efficiency of 23.11% PCE. [33] The vertical separation promoted the charge extraction and electron blocking properties of the device and improved the stability response when encapsulated in polyisobutylene, retaining 90% of its initial efficiency after exposure to 85 °C and 85% relative humidity for 1000 h. [33] In a remarkable study, Jeong et al reported the incorporation of gallium (III) acetylacetonate Ga(acac) 3 into P3HT HTL (Figure 3). [32] Ga(acac) 3 interacts with the perovskite surface, passivating the defects on the perovskite surface and reducing the interfacial trap-assisted recombination loss.…”
Section: Inorganic Additivesmentioning
confidence: 99%
“…As shown in Figure 9, the P3HT-based PSCs have shown a relatively stabilized performance, especially in the last years of the progress. [30][31][32] Compared to lithium-doped Spiro-OMeTAD PSCs, P3HT-based devices not only achieved higher efficiencies >23% PCEs compared to Spiro-based PSCs (≈21% PCEs), [30][31][32][33] but also showed a better tolerance to withstand harsh conditions and continuous illumination at MPP. [27][28][29] At the same conditions, Spiro-based devices show a very sharp decline in their efficiencies, whereas the perovskite layer underneath is observed to undergo clear degradation, yielding many impurity peaks shown by X-ray diffraction (XRD) measurements.…”
Section: Stability In P3ht-based Pscsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10] Currently, effective methods to improve the efficiency of PSCs involve advanced structural and material design, combined with high-quality passivation at perovskite-related interfaces and grain boundaries. [11][12][13][14][15][16][17][18] For instance, Xu et al introduced an insulator alumina nanoplate with random nanoscale openings between the perovskite absorber and transport layer to reduce contact area and minimize surface recombination. [19] This led to a high efficiency of 25.5% with remarkable open-circuit voltage (V OC , 1.208 V) and fill factor (FF, 84.37%) for a p-i-n PSC.…”
Section: Introductionmentioning
confidence: 99%